Valuing the past and looking to the future: the National Museum of Peru - Cigarini, Tommaso (2023)
This article on the National Museum of Peru (MUNA) shows a particular focus on its ori- gin, the architectural competition, the construction of the building and the history of the place where it is located. Likewise, the weaknesses and strengths of the museum are evaluated in relation to its distance from the center of Lima, technical aspects of its operation and, finally, its importance for the Peruvian nation. The architectural analysis is carried out from the spatial, functional and technological point of view, considering the relationship of the museum with the cultural and natural context.